Find the exact value of the expressions \( \cos (\alpha+\beta) \), \( \sin (\alpha+\beta) \) and \( \tan (\alpha+\beta) \) under the following conditions: \( \cos (\alpha)=\frac{24}{25}, \alpha \) lies in quadrant IV, and \( \sin (\beta)=\frac{-2}{5}, \beta \) lies in quadrant Ill. a. \( \cos (\alpha+\beta)=\frac{-24 \sqrt{21}-14}{125} \) (Simplify your answer. Type an exact answer, using radicals as needed. Rationalize all denominators. Use integers or fractions for any numbers in the expression.) b. \( \sin (\alpha+\beta)=\frac{7 \sqrt{21}-48}{125} \) (Simplify your answer. Type an exact answer, using radicals as needed. Rationalize all denominators. Use integers or fractions for any numbers in the expression.) c. tan \( (\alpha+\beta)=\square \) (Simplify your answer. Type an exact answer, using radicals as needed. Rationalize all denominators. Use integers or fractions for any numbers in the expression.)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To find \(\cos(\alpha + \beta)\), \(\sin(\alpha + \beta)\), and \(\tan(\alpha + \beta)\), we start by determining \(\sin(\alpha)\) and \(\cos(\beta)\) based on the given values of \(\cos(\alpha)\) and \(\sin(\beta)\). 1. **Finding \(\sin(\alpha)\)**: Since \(\cos(\alpha) = \frac{24}{25}\) and \(\alpha\) lies in the IV quadrant, we can use the Pythagorean identity: \[ \sin^2(\alpha) + \cos^2(\alpha) = 1 \implies \sin^2(\alpha) + \left(\frac{24}{25}\right)^2 = 1 \] Calculate \(\sin^2(\alpha)\): \[ \sin^2(\alpha) + \frac{576}{625} = 1 \implies \sin^2(\alpha) = 1 - \frac{576}{625} = \frac{49}{625} \] Thus, \[ \sin(\alpha) = -\sqrt{\frac{49}{625}} = -\frac{7}{25} \] 2. **Finding \(\cos(\beta)\)**: Given \(\sin(\beta)=\frac{-2}{5}\) and \(\beta\) lies in quadrant III, we use the Pythagorean identity again: \[ \sin^2(\beta) + \cos^2(\beta) = 1 \implies \left(\frac{-2}{5}\right)^2 + \cos^2(\beta) = 1 \] Calculate \(\cos^2(\beta)\): \[ \frac{4}{25} + \cos^2(\beta) = 1 \implies \cos^2(\beta) = 1 - \frac{4}{25} = \frac{21}{25} \] Thus, \[ \cos(\beta) = -\sqrt{\frac{21}{25}} = -\frac{\sqrt{21}}{5} \] 3. **Calculating \(\cos(\alpha + \beta)\)**: Now we apply the angle addition formula for cosine: \[ \cos(\alpha + \beta) = \cos(\alpha)\cos(\beta) - \sin(\alpha)\sin(\beta) \] Substituting our values: \[ \cos(\alpha + \beta) = \left(\frac{24}{25}\right)\left(-\frac{\sqrt{21}}{5}\right) - \left(-\frac{7}{25}\right)\left(-\frac{2}{5}\right) \] \[ = -\frac{24\sqrt{21}}{125} - \frac{14}{125} = \frac{-24\sqrt{21} - 14}{125} \] 4. **Calculating \(\sin(\alpha + \beta)\)**: Using the sine addition formula: \[ \sin(\alpha + \beta) = \sin(\alpha)\cos(\beta) + \cos(\alpha)\sin(\beta) \] Substituting our values: \[ \sin(\alpha + \beta) = \left(-\frac{7}{25}\right)\left(-\frac{\sqrt{21}}{5}\right) + \left(\frac{24}{25}\right)\left(-\frac{2}{5}\right) \] \[ = \frac{7\sqrt{21}}{125} - \frac{48}{125} = \frac{7\sqrt{21} - 48}{125} \] 5. **Calculating \(\tan(\alpha + \beta)\)**: We use the relationship \[ \tan(\alpha + \beta) = \frac{\sin(\alpha + \beta)}{\cos(\alpha + \beta)} \] Substituting the values we computed: \[ \tan(\alpha + \beta) = \frac{\frac{7\sqrt{21} - 48}{125}}{\frac{-24\sqrt{21} - 14}{125}} = \frac{7\sqrt{21} - 48}{-24\sqrt{21} - 14} \] Simplifying the negative form: \[ \tan(\alpha + \beta) = \frac{48 - 7\sqrt